2018
DOI: 10.21614/chirurgia.113.5.687
|View full text |Cite
|
Sign up to set email alerts
|

Tumor is an Oxidative Stress Factor in Ovarian Cancer Patients

Abstract: Introducere: Adenocarcinomul ovarian reprezintă la nivel global, a doua cauză de neoplazie în rândul tumorilor ginecologice, dar este principala cauză de mortalitate prin tumori ginecologice. Scopul acestui studiu a fost să identifice intensitatea stresului oxidative la pacienţii cu adenocarcinom ovarian şi să identifice relaţiile dintre diferite specii reactive de oxigen (ROS) şi prezenţa tumorii reziduale. Pacienţi şi metode: Treizeci-şi-cinci paciente cu adenocarcinom ovarian stadiul II-IV, diagnosticate în… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, recent studies have indicated that increased level of antioxidants are also prevalent in cancer cells to detoxify ROS and at the same time sustain enhanced mitogenic signaling to promote tumourigenesis, resistance to therapy and apoptosis [240]. Increased ROS production has been reported for ovarian tumours [241]. This may relate to genetic instability, DNA damage repair deficiency, enhanced aggressiveness and the chemoresistant phenotype of the disease as discussed previously.…”
Section: Role Of Magmas Inhibitor In Ovarian Cancer Treatmentmentioning
confidence: 89%
“…However, recent studies have indicated that increased level of antioxidants are also prevalent in cancer cells to detoxify ROS and at the same time sustain enhanced mitogenic signaling to promote tumourigenesis, resistance to therapy and apoptosis [240]. Increased ROS production has been reported for ovarian tumours [241]. This may relate to genetic instability, DNA damage repair deficiency, enhanced aggressiveness and the chemoresistant phenotype of the disease as discussed previously.…”
Section: Role Of Magmas Inhibitor In Ovarian Cancer Treatmentmentioning
confidence: 89%
“…Oxidative stress and ROS are involved in the development of various diseases including cancers. [ 51,52 ] However, within the tumor microenvironment, cancer cells have high basal oxidative stress with an induced antioxidant system, and therefore can evade ROS‐induced cell death. [ 53,54 ] Our EAC mouse model showed significantly increased MDA levels with decreased TAC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in another study the mean values of serum MDA and ceruloplasmin were significantly higher in patients with macroscopic residual tumour after surgery compared to patients without residual tumours, the study demonstrating that the tumour was an oxidative stress inducer [27].…”
Section: Resultsmentioning
confidence: 88%